2020
DOI: 10.3892/mmr.2020.11629
|View full text |Cite
|
Sign up to set email alerts
|

Human cathelicidin antimicrobial peptide suppresses proliferation, migration and invasion of oral carcinoma HSC-3 cells via a novel mechanism involving caspase-3 mediated apoptosis

Abstract: Human cathelicidin antimicrobial peptide and its active product, ll-37 (caMP/ll-37), exhibit a broad spectrum of antimicrobial effects. an increasing number of studies have shown that human caMP/ll-37 also serves significant roles in various types of cancer. The primary aims of the present study were to investigate the roles and mechanisms of human caMP/ll-37 in oral squamous cell carcinoma (oScc) cells. The results indicated that either ll-37 c-terminal deletion mutants (cdel) or caMP stable expression in HSc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…PG-1 (16 µM) did not impact the clonogenicity of glioma U251 cells over 7 days. Chen X. et al indicate that human LL-37 inhibits the clonogenicity and proliferation of oral squamous cell carcinoma HSC-3 cells through an increase in the expression of cyclin B1 and PKR-like ER kinase [ 28 ]. Inhibition of the p75NGFR receptor suppressed the clonogenicity of non-small cell H460 and lung carcinoma H1299 cells and stimulated their sensitivity to chemotherapy in a mouse xenograft model [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PG-1 (16 µM) did not impact the clonogenicity of glioma U251 cells over 7 days. Chen X. et al indicate that human LL-37 inhibits the clonogenicity and proliferation of oral squamous cell carcinoma HSC-3 cells through an increase in the expression of cyclin B1 and PKR-like ER kinase [ 28 ]. Inhibition of the p75NGFR receptor suppressed the clonogenicity of non-small cell H460 and lung carcinoma H1299 cells and stimulated their sensitivity to chemotherapy in a mouse xenograft model [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…LL-37 inhibits the migration and invasion of HSC-3 cells. In these cells, there is an increase in LL-37 gene expression CAMP and activation of caspase-3, with p53-Bcl-2/BAX-dependent apoptosis [ 28 ]. In contrast, LL-37 stimulates the internalization of the CXCR4 receptor, activation of the MAPK/Akt/PKC cascade, and migration and invasion of breast cancer MCF7 and MDA-MB-231 cells [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, via activating TRPV2 and PI3/Akt signaling, and then inducing recruitment of TRPV2 from intracellular vesicles to the plasma membrane of pseudopodia, LL-37 promotes proliferation and growth of breast cancer cells ( Farabaugh et al, 2016 ). On the contrary, it has also been shown that LL-37 can exert anticancer effects on other cancers, including colon cancer, glioblastoma, hematologic malignancy, gastric cancer, and oral squamous cell carcinoma ( Aarbiou et al, 2006 ; Wu et al, 2010b ; Bruns et al, 2015 ; Prevete et al, 2015 ; Chen et al, 2020 ; Porter et al, 2021 ; Chernov et al, 2022 ). There is no smoking gun to explain the reported opposite effects on different cancer types.…”
Section: How Ll-37 Can Eradicate/affect Cancer?mentioning
confidence: 99%
“…LL-37 might act as a tumor suppressor in oral squamous cell carcinoma. The mechanisms may involve the induction of caspase-3-mediated apoptosis via the P53-Bcl-2/BAX signalling pathway (Chen et al, 2020).…”
Section: Natural Antimicrobial Peptidesmentioning
confidence: 99%
“…LL‑37 might act as a tumor suppressor in oral squamous cell carcinoma. The mechanisms may involve the induction of caspase‐3‐mediated apoptosis via the P53‑Bcl‑2/BAX signalling pathway (Chen et al., 2020). However, LL37 had no effect on the progression of squamous cell carcinoma on the tongue (Vierthaler et al., 2020).…”
Section: Some Antimicrobial Peptides Are Tumor Suppressorsmentioning
confidence: 99%